2018
DOI: 10.1093/omcr/omx100
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured hepatic aneurysm as first presenting symptom of polyarteritis nodosa

Abstract: Polyarteritis nodosa (PAN) is an inflammatory vasculitis that creates regions of stenosis and aneurysm formation. The authors describe a 66-year-old female with hepatic artery rupture as the first presentation of undiagnosed PAN, presenting with abdominal pain followed by hemorrhagic shock. This aneurysm was suture ligated with a successful outcome. A mesenteric arteriogram demonstrated lesions consistent with PAN including aneurysms of the left gastric branches, right and left hepatic arteries, and beaded app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…A vasculitis such as polyarteritis nodosa has been reported to result in the formation of aneurysms. [5] Pseudoaneurysm formation can occur after trauma to the hepatic artery; furthermore, there have even been cases of pseudoaneurysm formation trauma from a percutaneous biopsy. [6] Diagnostic testing Before definitive treatment, most patients with known or suspected mycotic aneurysms undergo essential diagnostic testing, including complete blood count, comprehensive metabolic panel, gram stain, blood cultures, and sensitivities, as well as contrast-enhanced CT or magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vasculitis such as polyarteritis nodosa has been reported to result in the formation of aneurysms. [5] Pseudoaneurysm formation can occur after trauma to the hepatic artery; furthermore, there have even been cases of pseudoaneurysm formation trauma from a percutaneous biopsy. [6] Diagnostic testing Before definitive treatment, most patients with known or suspected mycotic aneurysms undergo essential diagnostic testing, including complete blood count, comprehensive metabolic panel, gram stain, blood cultures, and sensitivities, as well as contrast-enhanced CT or magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…A vasculitis such as polyarteritis nodosa has been reported to result in the formation of aneurysms. [ 5 ] Pseudoaneurysm formation can occur after trauma to the hepatic artery; furthermore, there have even been cases of pseudoaneurysm formation trauma from a percutaneous biopsy. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although aneurysms are common findings associated with PAN, large aneurysms are rarely reported in the SMA [1]. Previous case studies have reported rupturing of visceral arteries with aneurysm caused by PAN [6]. Litt et al.…”
Section: Discussionmentioning
confidence: 99%
“…An initial presentation with spontaneous intra-abdominal bleeding is unusual, but has the risk of a lethal outcome. [11,12] This makes adequate diagnosis, by means of visceral angiography, and subsequent (interventional) treatment necessary. [13] 4.…”
Section: Discussionmentioning
confidence: 99%